Myanmar Country Environmental Analysis : Assessing the Opportunities for Scaling Up Community Forestry and Community Forestry Enterprises in Myanmar - World Bank (World Bank, Washington, DC, 2019)
Rural communities in Myanmar have numerous economic, environmental, and social opportunities but also face challenges as they seek a clear and solid pathway to development. The Government of Myanmar (GoM), as well as several development and donor organizations, have recognized the potential of community forestry (CF) to address many of these challenges. This recognition has taken the form of targets for CF development (for example, 2.27 million acres [919,000 hectares (ha)] of community forests by fiscal year 2030/31), legal frameworks (for example, Community Forestry Instructions [CFIs], 1995 and 2016), and programs by state and non-state actors (NSAs).